Physiological and Pathogenic Contributors to the Summer Decline of Roughstalk Bluegrass. Issue 1 (19th October 2017) - Thompson, Cole; Kennelly, Megan; Fry, Jack; Sousek, Matt; Reicher, Zac
Abstract : Roughstalk bluegrass ( Poa trivialis L.) is a cool‐season perennial turfgrass species that is more sensitive to heat stress than other cool‐season grasses. This sensitivity has been associated with increased rates of respiration compared with photosynthesis, or an inability to hydrolyze carbohydrates to simple sugars for metabolism during heat stress, but may also involve common turfgrass diseases, since roughstalk bluegrass has been shown to maintain quality from repeated applications of strobilurin fungicides in summer. Our objective was to differentiate between physiological and pathogenic contributors to roughstalk bluegrass decline and determine the effects of strobilurin fungicides on its growth and physiology. Roughstalk bluegrass was treated with azoxystrobin (Heritage 50 WDG or Heritage TL) at 610 g a.i. ha −1 or pyraclostrobin (Insignia 20 WG or Insignia SC) at 556 g a.i. ha −1 prior to summer heat stress in field plots in Manhattan, KS, (2011 and 2012) and Mead, NE (2012). Fungicides improved quality and percentage green cover over untreated roughstalk bluegrass in all studies, but fungicides rarely affected rooting or rates of gross photosynthesis. Disease sampling did not reveal any fungal pathogen consistently associated with summer turf decline. Our data suggest that nontarget physiological effects of strobilurin fungicides likely increased quality and cover over untreated roughstalk bluegrass during summer.